Effective anti-doping testing program during major sport events: a comparative analysis of two multi-sport tournaments held in Poland in 2017 and 2023 - Lipska, E.; Szamotulska, K.; Kwiatkowska, D.; Rynkowski, M. (Frontiers in Sports and Active Living, 2025)
Introduction: Major Sporting Events (MSEs), particularly Multi-Sport Tournaments (MSTs), present significant logistical and operational challenges in the implementation of effective Anti-Doping Programs (ADPs). This study presents a comparative analysis of ADP implementation during two MSTs hosted in Poland: The World Games 2017 (TWG 2017) and the European Games 2023 (EG 2023).